Transforming Wheels: AI Revolution across the Automotive Value Chain - Mayank Rai (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transformative impact of artificial intelligence across the entire automotive value chain, from vehicle conceptualization and design through manufacturing, user experience, and business operations. The article analyzes how AI technologies revolutionize traditional automotive engineering paradigms through generative design algorithms, digital twins, and materials science applications. The article explores autonomous vehicle systems, detailing advances in perception, decision-making frameworks, validation methodologies, and computing architectures that enable increasingly sophisticated autonomous capabilities. Additionally, it investigates how AI enhances the in-vehicle experience through natural language processing, driver monitoring, predictive maintenance, and emotion recognition systems. The business operations section examines AI applications in customer segmentation, virtual showrooms, inventory management, mobility services, and usage-based insurance models. Finally, the article addresses critical challenges, including data privacy, safety certification, ethical considerations, cybersecurity risks, and workforce development needs. The article reveals how AI is not merely augmenting existing automotive systems but fundamentally redefining the industry’s technological foundations, business models, and consumer relationships.